Abrasive wear behavior of SiCp–Sialon composite refractories. Issue 7 (August 2015) - Li, Xiaochao; Chen, Shusen; Ding, Hao; Huang, Zhaohui; Liu, Baolin; Fang, Minghao; Liu, Yan׳gai; Wu, Xiaowen; Ma, Bin
Abstract: The abrasive wear tests were performed on the prepared SiCp –Sialon composite refractories with quartz particles as abrasives. The study aims to explore the effects of load and wear time on wear loss of SiCp –Sialon composite refractories as well as the mechanism of material removal. SiCp –Sialon composite refractories prepared by nitriding reaction sintering consisted of α-SiC, β-Si3 N4, and Si4 Al2 O2 N6 . The wear loss of SiCp –Sialon composite refractories increased significantly with the increases in test load and test time. The primary wear mechanism of SiCp –Sialon composite refractories is micro-cutting. The mechanism of material removal mainly involves the matrix. The micro-cutting occurred firstly in the matrix and caused the loss of the matrix. Without the protection from the surrounding matrix, the SiC aggregates were eventually stripped.